Os limites da soberania em Jean Bodin - Mello, Jezreel Antonio (Universidade do Vale do Rio dos Sinos, 2018)
The present dissertation aims to analyze if, in Jean Bodin’s theory of sovereignty, it is possible to identify the existence of limitations to the acts of that who holds the sovereignty in a Republic. As of the answer to this question, we will try to establish whether or not the concept of sovereignty presented by Bodin is coherent, based on the analysis of divergent perspectives in this regard. In this sense, three perspectives can be highlighted among Bodin's commentators. The first includes proponents of the thesis that points to a contradiction in Bodin's thinking, since he advocates for an absolute but not unlimited concept of sovereignty. In a second perspective are the proponents of the conciliatory thesis, which asserts the coherence of Bodin’s concept of sovereignty. There is also a third way, comprised by those commentators who defend a mixed position, which affirms the partial coherence of Bodin's concept of sovereignty. To undertake this research, we will initially analyze the limits of sovereignty in Bodin's theory of sovereignty, starting with some key concepts for the understanding of the author’s concept of sovereignty, then proceeding to the exposition and review of the limits established by Bodin to the exercise of sovereign power. Finally, a critical exposition of these limits will be made, addressing the opposing positions of the commentators who defend the coherence and the contradiction in Bodin's thought, and exposing some elements that could lead to a conciliatory reading of the presented ideas.
Keywords: Soberania; Jean Bodin; Absolutismo; Limites da soberania; Sovereignty; Jean Bodin; Absolutism; Limits of sovereignty; ACCNPQ::Ciências Humanas::Filosofia